KEPATUHAN WAJIB PAJAK UMKM DI KABUPATEN KUDUS SELAMA PANDEMI COVID–19 - Antika , Firda Novi; Budiman, Nita Andriyani; Mulyani , Sri (Universitas Nusantara PGRI Kediri, 2020)
Taxes are the national backbone. The financial condition of MSMEs during the Covid–19 pandemic has decreased. May 2020, tax revenue has decreased by 10,82%. Compilance to pay taxes is even more crucial in the midst of the large funding needs from the goverment. The study aims to analyze the compilance of MSME taxpayers in Kudus Regency during the Covid – 19 pandemic. The goverment needs to pay special attention to this sector because the contribution of MSMEs to the national economy is quite large. The sampling technique used purposive sampling with 51 respondents. Analysis techniques by using multiple regression techniques. The results of the research prove that the service quality of tax officers and tax socialization has a positive effect partially on taxpayer compilance, while tax sanctions, tax compilance costs, and financial conditions partially do not affect taxpayaer compliance.